2019
DOI: 10.1097/fjc.0000000000000705
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Inhaled Long-Acting Bronchodilators With Adverse Cardiovascular Outcomes in Patients With Stable COPD: A Bayesian Network Meta-Analysis of Randomized Controlled Trials

Abstract: A majority of existing studies have focused on the efficacy of inhaled long-acting bronchodilators (ILABs), such as long-acting muscarinic antagonists (LAMAs) and long-acting β2–agonists (LABAs), and LABAs combined with LAMAs in treating chronic obstructive pulmonary disease (COPD). The current meta-analysis aimed to investigate the correlation of ILABs with specific cardiovascular adverse events (CAEs). Five electronic databases, including PubMed, Embase, Cochrane Library, Scopus, and Web of Science were syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Our findings are consistent with results from a recent meta-analysis of RCTs showing an increased risk of cardiac failure among patients with stable COPD and receiving LABA therapy than patients receiving placebo (odds ratio, OR 1.70, 95% CI, 1.00–2.90). 35 Additional network meta-analysis results indicated that LABAs combined with LAMAs resulted in an increased risk of cardiac failure in patients with COPD compared with placebo (OR 2.32, 95% CI, 1.10–5.09). 35 Also, in another meta-analysis of 43 randomized trials, the authors reported that inhaled LABA increased the risk of cardiac failure (relative risk [RR] 1.71, 95% CI 1.04–2.84, I 2 27.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with results from a recent meta-analysis of RCTs showing an increased risk of cardiac failure among patients with stable COPD and receiving LABA therapy than patients receiving placebo (odds ratio, OR 1.70, 95% CI, 1.00–2.90). 35 Additional network meta-analysis results indicated that LABAs combined with LAMAs resulted in an increased risk of cardiac failure in patients with COPD compared with placebo (OR 2.32, 95% CI, 1.10–5.09). 35 Also, in another meta-analysis of 43 randomized trials, the authors reported that inhaled LABA increased the risk of cardiac failure (relative risk [RR] 1.71, 95% CI 1.04–2.84, I 2 27.5%).…”
Section: Discussionmentioning
confidence: 99%
“… 35 Additional network meta-analysis results indicated that LABAs combined with LAMAs resulted in an increased risk of cardiac failure in patients with COPD compared with placebo (OR 2.32, 95% CI, 1.10–5.09). 35 Also, in another meta-analysis of 43 randomized trials, the authors reported that inhaled LABA increased the risk of cardiac failure (relative risk [RR] 1.71, 95% CI 1.04–2.84, I 2 27.5%). 36 Furthermore, a recent nested-case control study indicated that new use of LABAs or LAMAs in patients with COPD is associated with an approximately 1.5-fold increase in severe cardiovascular risk, irrespective of prior CVD status and history of exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxical bronchospasm, laryngeal spasm, and swelling of the throat may occur. Long-acting beta-agonists (LABAs) increase the risk of heart failure in people with COPD [ 20 ].…”
Section: Salmeterolmentioning
confidence: 99%
“…Similarly, a meta-analysis showed that bronchodilator therapy increased the risk of heart failure in patients with stable COPD compared with placebo controls suggesting this long-term treatment needs to be used with caution in patients with or without cardiac conditions. 16 In this study, concomitant therapy was not associated with increased cardiac adverse events in patients with ALI and this could be due to the relative sample size.…”
Section: Discussionmentioning
confidence: 67%